The translation of ittaḥaẓa awliya and the rights of non-Muslims as leaders in Indonesia - Faizin, Nur (HTS teologiese studies, 2024)
This research aimed to show the political stance of the Muslim majority represented by the Ministry of Religious Affairs of the Republic of Indonesia (MoRA RI) towards non-Muslim leadership through the translation of the Qur’an. It examined the differences in the translation of the Qur’an based on the theory of translation as a political act. A total of 19 phrases or collocated words ittahaza awliya were found in the corpus of the Qur’an. The researchers approached the study with a critical discourse analysis approach, and conducted contrastive analysis on translations of these collocated words in four editions of translations of the Qur’an published officially by MoRA RI from 1965 to 2019. The results proved that interference in translation of the collocation ittaḥaẓa awliya is caused by the influence of the source text, and that the political situation and ideology influenced the translation of the Qur’an in Indonesia. The political direction of the Indonesian government, especially MoRA RI, tended to provide more opportunities for non-Muslims to become leaders today, as seen in the 2019 edition. While the translation edition published before tended to close the possibility of non-Muslims becoming leaders. This finding shows the government’s stance on democracy for non-Muslims, which according to previous research findings has declined with the rise of Islamic populism in Indonesia.Contribution: This article provides an explanation of one side of the difficulty of translating collocation [ittaḥaẓa awliya] in the Qur’an and at the same time shows the political direction of the government of the Republic of Indonesia regarding the politics of non-Muslim leadership.